2019
DOI: 10.1111/aspp.12498
|View full text |Cite
|
Sign up to set email alerts
|

Pivot Toward China: A Critical Analysis of the Philippines' Policy Shift on the South China Sea Disputes

Abstract: This article investigates the Philippines' puzzling reversal of its position against China following its victory in the Permanent Court of Arbitration (PCA) on maritime claims in the South China Sea. Instead of asserting its de jure sovereign rights, which were reaffirmed by the PCA's decision, Philippine President Rodrigo Duterte instead opted to build stronger relations with China. Proposing a burden sharing analytical approach, the article argues that the Philippines is using China as leverage in its allian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Finally, we would like to highlight a few promising areas for future research. First, as our findings have pointed out, whilst the Philippines continues to maintain its long‐standing alliance and cooperation with the United States (Lee 2020; Manantan 2019), global infrastructure developments, particularly China's Road and Belt programme, have been playing a crucial role in the country's spatial strategy, enabling China to rapidly extend its economic and military presence in the wider region. This clearly indicates that there is a geopolitical dimension, role, and implication of socio‐ecological fixes, which needs to be investigated further.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Finally, we would like to highlight a few promising areas for future research. First, as our findings have pointed out, whilst the Philippines continues to maintain its long‐standing alliance and cooperation with the United States (Lee 2020; Manantan 2019), global infrastructure developments, particularly China's Road and Belt programme, have been playing a crucial role in the country's spatial strategy, enabling China to rapidly extend its economic and military presence in the wider region. This clearly indicates that there is a geopolitical dimension, role, and implication of socio‐ecological fixes, which needs to be investigated further.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings show that, at the interregional scale, the fix offers spatio‐temporal opportunities and revenues for economic and political elites and their reach into the peripheries of the country. At the international scale, we have identified that this often goes hand‐in‐hand with the Philippines’ shift of geopolitical focus from the United States to China—particularly due to the latter's Belt and Road programme—offering long‐ and short‐term opportunities, while the country continues its long‐standing alliance and cooperation with the US (Lee 2020; Manantan 2019). Our case analysis shows that the SEA Games were used as an opportune platform to showcase the “Build, Build, Build” infrastructure programme, representing the flagship development agenda of the Philippine government (Philippine News Agency 2017), securing essential funding for its next building stages, attracting potential clients to the city, as well as boosting the tourism industry as the regional economy's backbone (Cervantes 2018; Go 2019; New Clark City Stadium 2019; Tecson 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continued presence of American troops following the country's independence in 1946 was perceived by many, including by Duterte himself, as 'residual colonialism' . 64 Many Filipinos felt that their country was not considered as an equal by the United States in diplomatic meetings, and this lack of consideration partly explains why Duterte wanted to distance himself from Washington. 65 But it was the Obama administration's criticism of his government's extrajudicial killings and human rights violations that triggered President Duterte's public defiance.…”
Section: Political Grievance and Perceived Lack Of Security Assurancementioning
confidence: 99%